Production function analysis of drif gill net fishing in Guimbal, Iloilo. - Gerochi, Mananita Y. (1991.)
This paper analyzed the productivity level of drift gill net, the major small-scale fishing gear in terms of number of units and fisherman employed, operating in Guimbal. The analysis used secondary data collected for 12 months by Padilla et. al, 1989., The production function approach using the Cobb-Douglas functional form was used to explain the variations in the value of catch of drift gill net fishermen. Five explanatory variables, namely, repair and maintenance of boat and engine, repair and maintenance of gear/net, actual fishing time, value of fuel and miscellaneous operating costs were included in the regression model. The F-test showed that the 5 explanatory variables were significantly different from zero. Three variables namely, actual fishing time, repair and maintenance of boat and engine and repair and maintenance of gear and net turned out significant in the T-test.
Thesis (Undergraduate, Bachelor of Science in Economics) College of Arts and Sciences, University of the Philippines in the Visayas, Iloilo City.
Keywords: Drift gill nets -- Fishing operations -- Guimbal, Iloilo